Synchronous Carotid Bifurcation Endarterectomy and Retrograde Kissing Stenting of the Innominate and Left Common Carotid Artery in a Patient with a Bovine Aortic Arch. (11th April 2017) - Robaldo, Alessandro; Carignano, Guido; Balderi, Alberto; Novali, Claudio
Abstract : Management of the symptomatic multiple stenosis of supra-aortic vessels (MSSVs) in a "bovine" aortic arch (BAA) configuration is infrequently reported. The optimal treatment choice remains debatable. A successful hybrid treatment for a proximal critical stenosis of the innominate and left common carotid artery was performed in a high-risk patient with a tandem symptomatic lesion in the right carotid bifurcation and a concentric vulnerable plaque in the bovine trunk. This case supports the feasibility, safety, and efficacy of a combined carotid bifurcation endarterectomy and retrograde kissing stenting of common carotid arteries with cerebral protection after evaluation of radiological, anatomical, and clinical parameters.